Reaction-type toughening oligomer containing interface anchoring group, preparation method thereof, and two-component acrylate structural adhesive and preparation method thereof
Patent Information
- Application Number
- CN202611132080.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-09-29
AI Technical Summary
[0007]基于此,本发明提供了一种含界面锚定基团的反应型增韧寡聚物及其制备方法、包含该寡聚物的双组份丙烯酸酯结构胶及其制备方法,旨在克服现有技术中增韧与界面增强功能分离、非反应型组分易迁移、湿热耐久性不足等缺陷,实现拉伸剪切强度、剥离韧性和湿热耐久性的协同提升
B组份的制备:在保护气氛下,将增塑剂、氧化剂、增韧剂、填料和颜料,在20℃~25℃混合均匀,抽真空脱泡,过滤出料。
Smart Images

Figure CN122832247A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of adhesive technology, and in particular to a reactive toughening oligomer containing interfacial anchoring groups and its preparation method, and a two-component acrylate structural adhesive and its preparation method. Background Technology
[0002] Two-component acrylic structural adhesives are widely used in the automotive, rail transportation, engineering machinery, electronics, energy storage equipment, building structural components, and composite material assembly fields due to their advantages such as fast room temperature curing, good applicability to various substrates, relatively low sensitivity to construction conditions, and suitability for filling and bonding large gaps.
[0003] To meet the comprehensive requirements of structural bonding applications for strength, toughness, durability, and process adaptability, existing two-component acrylic structural adhesives typically incorporate toughening components, adhesion promoters, crosslinking modifiers, and fillers. Common toughening methods include adding liquid rubber, core-shell particles, polyurethane-modified resins, or flexible acrylic oligomers; common adhesion promoters include adding acidic monomers, phosphate ester accelerators, and silane coupling agents.
[0004] However, the existing technology has the following shortcomings: First, although conventional non-reactive toughening agents can improve peel strength or impact toughness to a certain extent, their limited chemical bonding with the main acrylate network can easily lead to a decrease in the cohesive strength of the system, a weakening of the phase interface, and even migration, precipitation, or performance degradation in long-term use or in humid and hot environments.
[0005] Second, while conventional small molecule adhesion promoters help improve initial adhesion to metal, aluminum, galvanized sheet or composite material surfaces, they usually have low molecular weight and insufficient fixation ability in the cured network, making it difficult to simultaneously achieve long-term interface stability, moisture and heat retention rate and toughness improvement.
[0006] Therefore, there is an urgent need to develop a new functional component that can participate in the curing reaction of the two-component acrylate system, provide a flexible toughening effect in the cured network, and enhance the interfacial interaction with the surface of the substrate, so as to achieve a synergistic improvement in tensile shear strength, peel toughness and hygrothermal durability. Summary of the Invention
[0007] Based on this, the present invention provides a reactive toughening oligomer containing interface anchoring groups and its preparation method, and a two-component acrylate structural adhesive containing the oligomer and its preparation method, aiming to overcome the defects of existing technologies such as separation of toughening and interface enhancement functions, easy migration of non-reactive components, and insufficient damp heat durability, and to achieve synergistic improvement of tensile shear strength, peel toughness and damp heat durability.
[0008] A reactive toughening oligomer containing interfacial anchoring groups has the following general formula: Anchor-R2-LPQ-R3-CR1=CH2; in: Anchor represents the interface anchoring group; P represents the flexible backbone segment, which is polymerized from polyisocyanate and polyol containing the flexible backbone segment; L and Q independently represent the linking groups formed by the reaction of isocyanate and active hydrogen; R1 represents H or CH3; R2 and R3 represent C-C bond skeleton structures containing only C and H bonds.
[0009] The reactive toughening oligomer containing interface anchoring groups in this invention provides flexibility, stress buffering, and energy dissipation in the cured adhesive layer via the flexible backbone segment P. The L and Q linkers act as chemical bridges, stably bonding the flexible backbone to polymerizable double bonds and interface anchoring groups, ensuring the triple functions of flexible toughening, cross-linking curing, and interface anchoring are firmly anchored in the cured network without migration or precipitation. Furthermore, the urethane and urea groups possess strong polarity and hydrogen bond formation capabilities, enhancing physical cross-linking and cohesive energy between molecular chains, effectively promoting stress transfer and energy dissipation. The polymerizable unsaturated group (-CR1=CH2) participates in the cross-linking curing of the two-component acrylate system, allowing the oligomer to be introduced into the cured network via chemical bonds. The interface anchoring group Anchor enhances the interaction between the oligomer and the surface of the substrate, improving interfacial bonding strength and environmental stability. Therefore, this invention integrates flexible toughening segments, linking groups, polymerizable double bonds, and interface anchoring groups into a single oligomer molecule. This allows the oligomer to provide toughening through its flexible backbone, introduce a cross-linked network via polymerizable double bonds, and enhance interfacial bonding through interface anchoring groups. The synergistic effect of these four components simultaneously improves tensile shear strength, peel toughness, and hygrothermal durability.
[0010] In one embodiment, the interface anchoring group is selected from at least one of phosphate ester group and catechol group; the linking group formed by the reaction of isocyanate and active hydrogen is selected from at least one of carbamate group and urea group; and the active hydrogen is selected from at least one of hydroxyl and amino groups. The oligomer contains 0.5 mmol / g to 1.5 mmol / g of polymerizable unsaturated double bonds and 0.08 mmol / g to 0.4 mmol / g of interfacial anchoring groups.
[0011] In one embodiment, the raw materials for preparing the oligomer, by weight parts, include the following components: 10 parts to 35 parts of polyisocyanate; 45 parts to 75 parts of flexible polyol; 10 parts to 15 parts of acrylate with active hydrogen; 2 parts to 5 parts of a compound with an interface anchoring group; and 0.1 parts to 0.8 parts of a polymerization inhibitor.
[0012] In one embodiment, the polyisocyanate is selected from at least one of hexamethylene diisocyanate, isophorone diisocyanate and 4,4'-dicyclohexylmethane diisocyanate; the flexible polyol is selected from at least one of polypropylene glycol, polytetrahydrofuran ether glycol, polyadipate diol, dimer acid-based polyester diol, polycarbonate diol and hydroxyl-terminated liquid polybutadiene; the acrylate with active hydrogen is selected from at least one of hydroxyethyl (meth)acrylate and hydroxypropyl (meth)acrylate; the compound with an interface anchoring group is selected from at least one of hydroxyl-containing phosphoric acid compounds, amino-containing phosphoric acid compounds and hydroxyl-containing catechol compounds; the polymerization inhibitor is selected from at least one of hydroquinone and p-tert-butylcatechol.
[0013] A preparation method of the reactive toughening oligomer containing an interface anchoring group according to any one of the above items, comprising the following steps: subjecting flexible polyol to vacuum dehydration, then under a protective atmosphere, fully reacting polyisocyanate with the dehydrated flexible polyol at 75°C to 80°C to obtain an isocyanate-terminated prepolymer; cooling the temperature to 45°C to 65°C, adding a polymerization inhibitor and mixing uniformly; then dropwise adding acrylate with active hydrogen at 45°C to 65°C, completing the dropwise addition within 1h to 2h, then fully reacting at 55°C to 70°C; cooling the temperature to 45°C to 55°C, dropwise adding the compound with an interface anchoring group, completing the dropwise addition within 1h to 2h, then fully reacting at 45°C to 55°C until the NCO content is ≤ 0.5%, which is regarded as qualified; and after qualification, cooling the temperature to 25°C to 30°C, filtering and discharging to obtain the reactive toughening oligomer containing an interface anchoring group.
[0014] The preparation method of the present invention adopts a step-by-step synthesis strategy: forming an isocyanate-terminated prepolymer first, then quantitatively introducing polymerizable double bonds and interface anchoring groups sequentially. The reaction conditions of each step are mild, the operation is controllable, the process window is wide, and taking NCO content ≤ 0.5% as a clear end-point criterion ensures sufficient and complete reaction. The obtained oligomer has a definite structure and stable functional group content, and is suitable for industrial scale-up production.
[0015] In one embodiment, the polyisocyanate and the dehydrated flexible polyol are reacted at 75°C to 80°C for 3 to 4 hours. After adding acrylate containing active hydrogen, the reaction time at 55℃~70℃ is 1h~2h. After adding the compound with the interfacial anchoring group, the reaction time at 45℃~55℃ is 3h~4h.
[0016] A two-component acrylic structural adhesive, comprising component A and component B: Component A comprises the following raw materials in parts by weight: 50-75 parts per unit; 5 to 15 parts of the oligomer as described in any one of claims 1 to 4; 0.1 to 1 part reducing agent; Toughening agent 10 to 30 parts; Polymerization inhibitor 0.1 to 1 part; 0.1 to 2 parts of filler; Component B comprises the following raw materials in parts by weight: Plasticizer 30-45 parts; 40 to 50 parts of oxidizing agent; Toughening agent 10 to 20 parts; Pigment 0.5 to 2 parts; 1 to 5 parts of filler.
[0017] The two-component acrylic structural adhesive of the present invention contains the above-mentioned reactive toughening oligomers and achieves rapid room temperature curing through an oxidation-reduction initiation system. The components are rationally proportioned and synergistically enhance each other. The structural adhesive exhibits excellent adhesion to a variety of substrates, high initial mechanical strength, and retains more than 75% of its shear strength, peel strength, and impact strength after 1000 hours of aging with double 85. It combines high strength, high toughness, and excellent long-term damp heat durability, making it suitable for high-requirement structural bonding in the automotive, rail transportation, and electronics industries.
[0018] In one embodiment, the monomer in component A is selected from at least one of methyl methacrylate, ethyl methacrylate, butyl methacrylate, methacrylic acid, and hydroxyethyl methacrylate. The reducing agent is selected from at least one of triethylamine and N,N-dimethyl-p-toluidine; The toughening agent is selected from at least one of nitrile rubber, chloroprene rubber, MBS resin, ABS resin, and SBS; The polymerization inhibitor is selected from at least one of hydroquinone, benzoquinone, naphthoquinone, and di-tert-butylmethylphenol; The filler is selected from fumed silica.
[0019] In one embodiment, the plasticizer in component B is selected from at least one of dioctyl dioacetate and dioctyl sebacate; The oxidant is benzoyl peroxide; The toughening agent is selected from at least one of nitrile rubber, chloroprene rubber, MBS resin, ABS resin and SBS; The filler is fumed silica; The pigment is phthalocyanine blue.
[0020] A method for preparing the two-component acrylic structural adhesive according to any one of the above claims includes the following steps: Preparation of component A: Under a protective atmosphere, the reactive toughening oligomer containing interfacial anchoring groups, monomers and polymerization inhibitors are mixed evenly at 20℃~25℃. Then, toughening agent, reducing agent and filler are added and mixed evenly. Vacuum degassing is performed and the mixture is filtered out. Preparation of Component B: Under a protective atmosphere, plasticizer, oxidant, toughening agent, filler and pigment are mixed evenly at 20℃~25℃, vacuum degassing is performed, and the mixture is filtered out.
[0021] The preparation method of this invention uses components A and B to be formulated separately, which effectively avoids premature contact between oxidant and reducing agent to induce polymerization; the temperature is controlled at 20℃~25℃ throughout the process and supplemented with a protective atmosphere to prevent premature polymerization caused by high temperature and oxygen inhibition of polymerization; vacuum degassing ensures that the adhesive layer is dense and free of bubbles, ensuring the reliability of bonding; the whole process is simple, has a wide operating window, is suitable for large-scale production, and has good industrial applicability. Attached Figure Description
[0022] Figure 1 This is a flowchart of a method for preparing a reactive toughening oligomer containing interface anchoring groups according to an embodiment of the present invention. Detailed Implementation
[0023] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. Many specific details are set forth in the following description to provide a thorough understanding of the present invention. However, the present invention can be practiced in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0025] A reactive toughening oligomer containing interface anchoring groups according to one embodiment of the present invention has the following general formula: Anchor-R2-LPQ-R3-CR1=CH2; in: Anchor represents the interface anchoring group; P represents the flexible backbone segment, which is polymerized from polyisocyanate and polyol containing the flexible backbone segment; L and Q independently represent the linking groups formed by the reaction of isocyanate and active hydrogen; where active hydrogen refers to active hydrogen (H) that can react with isocyanate. + ); R1 represents H or CH3; R2 and R3 represent C-C bond skeleton structures containing only C and H, such as straight-chain saturation (i.e., -(CH2)n-). Specifically, R2 can be -(CH2)2-, and R3 can be -(CH2)2- or -(CH2)3-.
[0026] The reactive toughening oligomer containing interface anchoring groups in this embodiment provides flexibility, stress buffering, and energy dissipation in the cured adhesive layer via the flexible backbone segment P. The L and Q linkers act as chemical bridges, stably bonding the flexible backbone to polymerizable double bonds and interface anchoring groups, ensuring the triple functions of flexible toughening, cross-linking curing, and interface anchoring are firmly anchored in the cured network without migration or precipitation. Furthermore, the urethane and urea groups possess strong polarity and hydrogen bonding ability, enhancing physical cross-linking and cohesive energy between molecular chains, effectively promoting stress transfer and energy dissipation. The polymerizable unsaturated group (-CR1=CH2) participates in the cross-linking curing of the two-component acrylate system, allowing the oligomer to be introduced into the cured network via chemical bonds. The interface anchoring group Anchor enhances the interaction between the oligomer and the surface of the substrate, improving interfacial bonding strength and environmental stability.
[0027] Based on the aforementioned embodiments, the interfacial anchoring group is selected from at least one of phosphate ester groups and catechol groups; the linking group formed by the reaction of isocyanate and active hydrogen is selected from at least one of urethane groups and urea groups; and the active hydrogen is selected from at least one of hydroxyl and amino groups. In this embodiment, on the one hand, the urethane ester group and urea group act as chemical bridges to stably bond the flexible backbone, polymerizable double bonds, and anchoring group. Their strong polarity and hydrogen bond formation ability can enhance the physical crosslinking and cohesive energy between molecular chains, promote stress transfer and energy dissipation, and prevent the toughening components from migrating and precipitating out during long-term use or in humid and hot environments. On the other hand, the phosphate ester group or catechol group anchoring group can form strong interactions such as coordination bonds or hydrogen bonds with the surface of substrates such as metals and aluminum, significantly enhancing the interfacial bonding strength and environmental stability. The synergy of these two aspects allows the oligomer to effectively toughen through the flexible backbone and firmly anchor to the surface of the adhered substrate after curing, thereby simultaneously improving the tensile shear strength, peel toughness, and humid and hot durability of the two-component acrylic structural adhesive.
[0028] Based on the aforementioned embodiments, the content of polymerizable unsaturated double bonds in the oligomer is 0.5 mmol / g to 1.5 mmol / g, and the content of interfacial anchoring groups is 0.08 mmol / g to 0.4 mmol / g. Controlling the double bond content to 0.5 mmol / g to 1.5 mmol / g ensures that the oligomer fully participates in the cross-linking and curing reaction, fixing itself in the network as a chemical bond, while avoiding excessive double bonds leading to over-cross-linking and loss of flexibility. Controlling the anchoring group content to 0.08 mmol / g to 0.4 mmol / g provides sufficient interfacial anchoring sites to enhance interfacial bonding strength, while avoiding excessive polar groups that could decrease system compatibility or shorten operating time. This selection of content range reflects the precise control of multiple performance balances in this invention. Furthermore, the content of polymerizable unsaturated double bonds in the oligomer may be, but is not limited to, 0.5 mmol / g, 1.0 mmol / g, or 1.5 mmol / g, and the content of interfacial anchoring groups may be, but is not limited to, 0.08 mmol / g, 0.16 mmol / g, 0.24 mmol / g, 0.32 mmol / g, or 0.4 mmol / g.
[0029] Based on the aforementioned embodiments, the raw materials for preparing the oligomers, according to parts by mass, include the following components: 10 to 35 parts of polyisocyanate; 45 to 75 parts of flexible polyol; 10 to 15 parts of acrylate containing active hydrogen; Two to five parts of a compound containing an interface anchoring group; and Polymerization inhibitor: 0.1 to 0.8 parts.
[0030] In this embodiment, polyisocyanate and flexible polyol constitute the main backbone of the flexible main chain segment; acrylate with active hydrogen is used to introduce polymerizable double bonds; compounds with interfacial anchoring groups are used to introduce anchoring function; and polymerization inhibitors ensure the stability of double bonds during synthesis. The reasonable combination of the dosage ranges of each component ensures that the molecular weight, double bond content, and anchoring group content of the resulting oligomer are all within the optimal range, thereby guaranteeing the overall performance of the final product.
[0031] Based on the aforementioned embodiments, the polyisocyanate is selected from at least one of hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), and 4,4'-dicyclohexylmethane diisocyanate (HMDI). Aliphatic diisocyanates possess excellent resistance to yellowing and good reactivity, enabling them to readily polymerize with flexible polyols to form flexible backbone segments. These types of polyisocyanates are available commercially from sources such as Wanhua Chemical.
[0032] Based on the aforementioned embodiments, the flexible polyol is selected from at least one of polypropylene glycol, polytetrahydrofuran ether glycol, polyadipate glycol, dimer acid polyester glycol, polycarbonate glycol, and hydroxyl-terminated liquid polybutadiene. The number average molecular weight of these flexible polyols is preferably 500-3000, more preferably 1000-2000. The flexible polyol provides flexibility and energy dissipation capacity to the main chain, forming the structural basis for the toughening function. These types of flexible polyols are commercially available, such as common polyether polyols like Dow polyether 1000LM and polyether 2000LM; polycarbonate glycols like Wanhua Chemical's WHP-HD series; and polytetrahydrofuran ether glycols like PTMEG-1000 and PTMEG-2000 from PTG (Korea).
[0033] Based on the aforementioned embodiments, the acrylate with active hydrogen is selected from at least one of hydroxyethyl (meth)acrylate and hydroxypropyl (meth)acrylate. The hydroxyl groups in its molecule can react with isocyanates to form urethane bonds, thereby introducing polymerizable double bonds into the oligomer terminus, enabling the oligomer to participate in free radical cross-linking and curing.
[0034] Based on the aforementioned embodiments, the compound with the interface anchoring group is selected from at least one of hydroxyphosphate compounds, aminophosphate compounds, and hydroxycatechol compounds, with phosphate esters, such as ethanolamine phosphate, being preferred. These compounds contain active hydrogen (hydroxyl or amino groups), which can react with isocyanates to form chemical bonds. Simultaneously, their phosphate ester or catechol groups can form strong interactions (such as coordination bonds, hydrogen bonds, etc.) with the surface of substrates such as metals and aluminum, thereby enhancing the interfacial bonding strength.
[0035] Based on the aforementioned embodiments, the polymerization inhibitor is selected from at least one of hydroquinone and p-tert-butylcatechol. These types of polymerization inhibitors are used to prevent premature polymerization of polymerizable double bonds during the synthesis process.
[0036] This invention integrates flexible toughening segments, linker groups, polymerizable double bonds, and interface anchoring groups into a single oligomer molecule. This allows the oligomer to provide toughening through its flexible backbone, introduce a cross-linked network via polymerizable double bonds, and enhance interfacial bonding through the interface anchoring groups. The synergistic effect of these four components simultaneously improves tensile shear strength, peel toughness, and hygrothermal durability.
[0037] Please see Figure 1 A method for preparing a reactive toughening oligomer containing interface anchoring groups according to an embodiment of the present invention includes the following steps: S10. The flexible polyol is dehydrated under vacuum, and then the polyisocyanate and the dehydrated flexible polyol are reacted fully at 75℃~80℃ under a protective atmosphere to obtain an isocyanate-terminated prepolymer.
[0038] In step S10, the operation of vacuum dehydrating the flexible polyol is as follows: the flexible polyol is added into a dry and impurity-free reaction vessel, the temperature inside the vessel is raised to 100℃~110℃, and then a vacuum is applied at -0.1MPa for 2h~3h. The material is then discharged into a dry HDPE barrel for later use.
[0039] In step S10, the protective atmosphere may be, but is not limited to, nitrogen.
[0040] In one embodiment, the polyisocyanate and the dehydrated flexible polyol are reacted at 75°C to 80°C for 3 to 4 hours to ensure complete polymerization of the polyisocyanate and flexible polyol to form a prepolymer.
[0041] After the reaction is carried out at a high temperature for 3 to 4 hours, the NCO content is measured. If it is close to the theoretical solid content, it is considered qualified, and the next step is carried out after passing the test.
[0042] S20, cool to 45℃~65℃, add polymerization inhibitor and mix well; then add acrylate with active hydrogen dropwise at 45℃~65℃, complete the addition within 1h~2h, and then react fully at 55℃~70℃.
[0043] In one embodiment, after the acrylate containing active hydrogen is added dropwise, the reaction is carried out at 55°C to 70°C for 1 to 2 hours to ensure the quantitative introduction of polymerizable double bonds.
[0044] S30. Cool down to 45℃~55℃, add the compound with the interface anchoring group dropwise, and finish the addition within 1h~2h. Then react fully at 45℃~55℃ until the NCO content is ≤0.5%, which is considered qualified.
[0045] In one embodiment, after adding the compound with the interface anchoring group, the reaction is carried out at 45°C to 55°C for 3 to 4 hours to ensure sufficient incorporation of the anchoring group.
[0046] It should be noted that if the compound with the interface anchoring group is a solid, it should be dissolved in an anhydrous solvent before being added dropwise, and then the solvent should be removed.
[0047] In this invention, the optimized combination of reaction times in each step ensures that the resulting oligomers have a uniform molecular structure and a stable content of functional groups.
[0048] S40. After passing the test, cool the material to 25℃~30℃, filter and discharge to obtain the reactive toughening oligomer containing interfacial anchoring groups.
[0049] In step S40, the material is filtered through a 200-mesh filter and discharged into a black HDPE drum.
[0050] The reaction mechanism of the reactive toughening oligomer containing interface anchoring groups according to one embodiment is as follows: S10. Synthesis of NCO-terminated flexible backbone segments (taking diisocyanate and polyether diol as examples): ; S20. Incorporating double bonds into the flexible main chain segment (using hydroxypropyl methacrylate as an example): ; S30. Incorporate interfacial anchoring groups (taking phosphate ester groups as an example) onto the flexible main chain segment containing double bonds: ; R4 represents the structure of the diisocyanate excluding the NCO group; R5 represents the structure of the polyether diol excluding the OH group.
[0051] The preparation method of this invention adopts a stepwise synthesis strategy. First, an isocyanate-terminated prepolymer is formed, and then polymerizable double bonds and interfacial anchoring groups are introduced sequentially and quantitatively. The reaction conditions of each step are mild, the operation is controllable, and the process window is wide. The NCO content ≤0.5% is used as a clear endpoint criterion to ensure that the reaction is complete. The resulting oligomer has a clear structure and stable content of functional groups, which is suitable for industrial-scale production.
[0052] One embodiment of the two-component acrylic structural adhesive includes component A and component B: Component A comprises the following raw materials in parts by weight: 50-75 parts per unit; 5 to 15 parts of the oligomer as described in any one of claims 1 to 4; 0.1 to 1 part reducing agent; Toughening agent 10 to 30 parts; Polymerization inhibitor 0.1 to 1 part; 0.1 to 2 parts of filler; Component B comprises the following raw materials in parts by weight: Plasticizer 30-45 parts; 40 to 50 parts of oxidizing agent; Toughening agent 10 to 20 parts; Pigment 0.5 to 2 parts; 1 to 5 parts of filler.
[0053] In this embodiment, the amount of oligomer in component A is 5 to 15 parts. Within this range, its toughening and interface enhancement functions can be fully utilized without affecting the overall crosslinking density and mechanical balance of the system due to excessive dosage. The oxidant in component B and the reducing agent in component A form a redox initiation system, achieving rapid curing at room temperature. This formulation system is complete, and the components work synergistically to achieve excellent mechanical properties and humid heat durability.
[0054] Based on the aforementioned embodiments, the monomers in component A are selected from at least one of methyl methacrylate, ethyl methacrylate, butyl methacrylate, methacrylic acid, and hydroxyethyl methacrylate. The selection of various methacrylate monomers can adjust the polarity, hardness, and curing speed of the system according to specific application requirements.
[0055] Based on the aforementioned embodiments, the reducing agent is selected from at least one of triethylamine and N,N-dimethyl-p-toluidine. Tertiary amine reducing agents and peroxides constitute a highly efficient redox initiation system.
[0056] Based on the aforementioned embodiments, the toughening agent is selected from at least one of nitrile rubber, chloroprene rubber, MBS resin, ABS resin, and SBS. The polymeric elastomer toughening agent and the oligomer of the present invention form a synergistic toughening effect.
[0057] Based on the aforementioned embodiments, the polymerization inhibitor is selected from at least one of hydroquinone, benzoquinone, naphthoquinone, and di-tert-butylmethylphenol.
[0058] Based on the aforementioned embodiments, the filler is selected from fumed silica. Fumed silica, as a thixotropic agent, imparts good workability to the adhesive.
[0059] Based on the aforementioned embodiments, the plasticizer in component B is selected from at least one of dioctyl dicarboxylate and dioctyl sebacate.
[0060] Based on the aforementioned embodiments, the oxidant is benzoyl peroxide. Benzoyl peroxide is a commonly used, highly efficient oxidant and is well-matched with tertiary amine reducing agents.
[0061] Based on the aforementioned embodiments, the toughening agent is selected from at least one of nitrile rubber, neoprene rubber, MBS resin, ABS resin, and SBS. The polymeric elastomer toughening agent further enhances the film-forming properties and flexibility of component B.
[0062] Based on the aforementioned embodiments, the filler is fumed silica. Fumed silica is used to adjust the rheological properties of component B.
[0063] Based on the aforementioned embodiments, the pigment is phthalocyanine blue. Phthalocyanine blue is used as a marker pigment to facilitate the differentiation of components A and B.
[0064] The two-component acrylic structural adhesive of the present invention contains the above-mentioned reactive toughening oligomers, and achieves rapid room temperature curing through an oxidation-reduction initiation system. The components are rationally proportioned and synergistically enhance each other. The adhesive exhibits excellent bonding performance to a variety of substrates, high initial mechanical strength, and retains more than 75% of its shear strength, peel strength, and impact strength after 1000 hours of aging at double 85. It combines high strength, high toughness, and excellent long-term damp heat durability, making it suitable for high-requirement structural bonding in the automotive, rail transportation, and electronics industries.
[0065] A method for preparing a two-component acrylic structural adhesive according to an embodiment of the present invention includes the following steps: Preparation of component A: Under a protective atmosphere, the reactive toughening oligomer containing interfacial anchoring groups, monomers and polymerization inhibitors are mixed evenly at 20℃~25℃. Then, toughening agent, reducing agent and filler are added and mixed evenly. Vacuum degassing is performed and the mixture is filtered out. Preparation of Component B: Under a protective atmosphere, plasticizer, oxidant, toughening agent, filler and pigment are mixed evenly at 20℃~25℃, vacuum degassing is performed, and the mixture is filtered out.
[0066] Specifically, the preparation of component A can be as follows: In a dry and impurity-free planetary mixer, a reactive toughening oligomer containing interfacial anchoring groups, a monomer, and a polymerization inhibitor are added sequentially, and nitrogen is used for purging. The jacket is turned on to control the temperature, and the temperature inside the reactor is maintained between 20℃ and 25℃ throughout the process. The mixture is stirred for 0.5h to 1h, and after it becomes uniform, the toughening agent is added. The mixture is stirred for 2h to 5h until the toughening agent is completely dissolved. Then, the reducing agent and filler are added, and the mixture is stirred for 1h to 2h. After it is fully dissolved, the mixture is degassed under vacuum at -0.09MPa for 10min. The mixture is then filtered through a 200-mesh filter into a 10:1 tube containing component A for later use.
[0067] Specifically, the preparation of component B can be as follows: plasticizer, oxidant, toughening agent, filler, and pigment are added to a dry and impurity-free planetary stirrer. After nitrogen purging, the temperature inside the reactor is controlled at 20℃~25℃ throughout the process. Stirring is carried out for 1h~2h, and vacuum degassing is performed at -0.09MPa for 10min. The mixture is then filtered through a 200-mesh filter into a 10:1 tube containing component B. After centrifugation, the bubbles are removed, and the mixture is ready for testing.
[0068] When using the two-component acrylic structural adhesive of the present invention, the volume ratio of component A to component B can be configured in a ratio of 10:1.
[0069] The preparation method of this invention uses components A and B to be formulated separately, which effectively avoids premature contact between oxidant and reducing agent to induce polymerization; the temperature is controlled at 20℃~25℃ throughout the process and supplemented with a protective atmosphere to prevent premature polymerization caused by high temperature and oxygen inhibition of polymerization; vacuum degassing ensures that the adhesive layer is dense and free of bubbles, ensuring the reliability of bonding; the whole process is simple, has a wide operating window, is suitable for large-scale production, and has good industrial applicability.
[0070] Referring to the above embodiments, in order to make the technical solution of the present invention more specific, clear and easy to understand, examples of the technical solution of the present invention are given below. However, it should be noted that the content to be protected by the present invention is not limited to the following embodiments.
[0071] Examples 1-3 (reactive toughening oligomers containing interfacial anchoring groups, labeled PUAP1-3) and Comparative Example 1 (a compound without interfacial anchoring groups, labeled PUAP0). The preparation method is as follows: 1. Weigh each raw material according to Table 1, add flexible polyol to a dry and impurity-free reaction vessel, heat the vessel to 110 degrees, then apply a vacuum of -0.1MPa for 2 hours, and discharge the material into a dry HDPE barrel for later use. 2. Add polyisocyanate to another dry and impurity-free reaction vessel, purge the air in the vessel with nitrogen, then add dehydrated flexible polyol, heat the vessel to 80°C, keep the reaction at this temperature for 4 hours, and measure the NCO content as shown in Table 2. If it is close to the theoretical solid content, it is considered qualified. After passing the qualification, proceed to the next step. 3. Cool to 60 degrees Celsius and add polymerization inhibitor; 4. Maintain 60 degrees Celsius and add acrylate containing active hydrogen dropwise over 1 hour. Then keep the temperature constant for 2 hours. Cool down to 50 degrees Celsius and completely dissolve O-phosphoethanolamine in 5 times the volume of anhydrous DMF. Then add the compound with interfacial anchoring groups dropwise over 1 hour. Then keep the temperature constant at 55 degrees Celsius for 4 hours. If the NCO content is ≤0.5% as shown in Table 2, it is considered qualified. After passing the test, evacuate to -0.1 MPa and keep it for 30 minutes before removing the solvent. 5. Cool down to 25 degrees Celsius, filter through a 200-mesh filter and discharge into a black HDPE barrel to obtain a reactive toughening oligomer containing interfacial anchoring groups, denoted as PUAP.
[0072] Table 1. Raw material list for Examples 1-3 and Comparative Example 1 Table 2. NCO content in Examples 1-3 and Comparative Example 1 Examples 4-6 and Comparative Examples 2-4 (Two-component acrylic structural adhesives) Preparation method of component A: According to Table 3, weigh each raw material and add the reactive toughening oligomer containing interfacial anchoring groups, monomer, and polymerization inhibitor sequentially into a dry and impurity-free planetary mixer. Replace with nitrogen, turn on the jacket to control the temperature, and maintain the temperature inside the reactor at 20 degrees Celsius throughout the process. Stir for 1 hour, and after uniformity, add the toughening agent and stir for 4 hours until the toughening agent is completely dissolved. Then add the reducing agent and filler, and stir for 0.5 hours. After fully dissolving and dispersing, vacuum at -0.09 MPa for 10 minutes to remove bubbles, and filter through a 200-mesh filter into a 10:1 tube of component A for later use.
[0073] In Table 3, A1, A2, and A3 correspond to component A in the two-component acrylic structural adhesives of Examples 4 to 6, respectively, while A4, A5, and A6 correspond to component A in the two-component acrylic structural adhesives of Examples 2 to 4, respectively.
[0074] Table 3 Formulation of Component A of Two-Component Acrylic Structural Adhesive Preparation method of component B: According to Table 4, weigh each raw material, add plasticizer, oxidant, toughening agent, filler and pigment in a dry and impurity-free planetary stirrer, replace with nitrogen, control the temperature inside the reactor at 20 degrees throughout the process, stir for 1 hour, vacuum degas at -0.09MPa for 10 minutes, filter through a 200-mesh filter into a 10:1 tube of component B, centrifuge and remove bubbles, and then test.
[0075] Table 4 Formulation of Component B of Two-Component Acrylic Structural Adhesive Performance testing: The performance of the two-component acrylic structural adhesives of Examples 4-6 and Comparative Examples 2-4 was tested. The test contents are as follows, and the test results are shown in Table 5.
[0076] 1. Shear strength: Tested using a universal electronic testing machine in accordance with GB / T 7124-2008 "Determination of tensile shear strength of adhesives (rigid material to rigid material)" standard; 2. Peel strength: Tested using a universal electronic testing machine in accordance with GB / T 2791-1995 "Test method for peel strength of adhesives - flexible materials to flexible materials". 3. Impact strength: Tested using a pendulum impact strength tester in accordance with GB / T 6328-2021 "Test Method for Shear Impact Strength of Adhesives".
[0077] Note: The aluminum test substrate is only pretreated with solvent and does not require sandblasting, grinding or other treatments. After mixing components A and B in a volume ratio of 10:1, the aluminum test substrate is bonded together. Ten substrates are bonded in each group, and the average value is taken. After being placed in a constant temperature and humidity chamber (23±2℃, 50±5%) for 24 hours, the test is performed under constant temperature and humidity conditions. After the double 85 test, the substrate is placed in a constant temperature and humidity chamber for 24 hours before the test.
[0078] Table 5 Performance test results of the two-component acrylic structural adhesives in the examples and comparative examples. Note: To better demonstrate the advantages of this invention, all embodiments and comparative examples use the same component B.
[0079] The following conclusions can be drawn from Table 5: 1. Initial Mechanical Property Analysis From the initial shear strength perspective, Examples 4-6, which incorporated reactive toughening oligomers containing interfacial anchoring groups, all exhibited excellent shear strength (≥17.9 MPa), with Example 5 showing the best performance (18.9 MPa) due to its higher content of phosphate ester groups. Comparative Example 2 (without anchoring groups) had a shear strength of 16.5 MPa, while Comparative Example 4 (without oligomers) only had 15.5 MPa. This demonstrates that the introduction of the oligomers of this invention can effectively improve shear strength.
[0080] In terms of initial peel strength, the peel strength of Examples 4-6 is ≥9.5 N / mm, which is significantly better than that of Comparative Example 2 (8.4 N / mm) and Comparative Example 4 (6.2 N / mm). The peel strength of Comparative Example 3 (with an anchoring group compound added in a blending manner) is 9.2 N / mm, which is close to the level of the Examples, indicating that the anchoring group contributes to the initial peel strength.
[0081] In terms of initial impact strength, the impact strength of Examples 4-6 is ≥11.6 kJ / m², which is significantly better than that of Comparative Example 2 (9.8 kJ / m²) and Comparative Example 4 (4.6 kJ / m²). The impact strength of Comparative Example 3 is 11.2 kJ / m², which is close to the level of the Examples.
[0082] 2. Analysis of damp heat aging performance After aging at 85°C and 85%RH for 1000 hours, the shear strength retention rate of Examples 4 to 6 was ≥78.8% (79.9% for Example 4, 80.4% for Example 5, and 78.8% for Example 6), the peel strength retention rate was ≥78.4% (78.9% for Example 4, 81.8% for Example 5, and 78.4% for Example 6), and the impact strength retention rate was ≥77.5% (79.3% for Example 4, 83.8% for Example 5, and 77.5% for Example 6).
[0083] Comparative Example 2 (without anchoring groups) showed a shear strength retention rate of only 70.9%, a peel strength retention rate of only 72.6%, and an impact strength retention rate of only 72.4%. Comparative Example 3 (anchoring groups added in a blending manner) showed a shear strength retention rate of 72.0%, a peel strength retention rate of 70.7%, and an impact strength retention rate of 74.1%. Comparative Example 4 (without oligomers) exhibited the most severe performance degradation, with a shear strength retention rate of only 65.2%, a peel strength retention rate of only 61.3%, and an impact strength retention rate of only 65.2%.
[0084] 3. Comparative Analysis Conclusions Although the initial properties of Comparative Example 3 (with the addition of an anchoring group compound via blending) were close to those of the Examples, its performance retention rate after aging was significantly lower than that of the Examples. This indicates that attaching the anchoring group to the oligomer backbone via chemical bonding, compared to simple blending, can more effectively fix the anchoring group in the cured network, preventing its migration and loss in humid and hot environments, thereby significantly improving long-term durability.
[0085] The above results indicate that by chemically linking interface anchoring groups to reactive toughening oligomers, the present invention achieves a synergistic effect of toughening and interface enhancement, significantly improving the tensile shear strength, peel toughness, and wet heat durability of the two-component acrylic structural adhesive.
[0086] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0087] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A reactive toughening oligomer containing interfacial anchoring groups, characterized in that, has the following general formula: Anchor-R2-L-P-Q-R3-CR1=CH2; wherein: Anchor represents an interface anchoring group; P represents a flexible main chain segment, which is polymerized from polyisocyanate and a polyol containing a flexible chain segment; L and Q each independently represent a linking group formed by the reaction of an isocyanate group and active hydrogen; R1 represents H or CH3; R2 and R3 represent a C-C bond skeleton structure containing only C and H.
2. The reactive toughening oligomer containing interface anchoring groups according to claim 1, characterized in that, The interface anchoring group is selected from at least one of a phosphate ester group and a catechol group; the linking group formed by the reaction of an isocyanate group and active hydrogen is selected from at least one of a carbamate group and a ureylene group; the active hydrogen is selected from at least one of a hydroxyl group and an amino group; The content of polymerizable unsaturated double bonds in the oligomer is 0.5 mmol / g to 1.5 mmol / g, and the content of the interface anchoring group is 0.08 mmol / g to 0.4 mmol / g.
3. The reactive toughening oligomer containing interface anchoring groups according to claim 1, characterized in that, In parts by mass, the raw materials for preparing the oligomer comprise the following components: 10 parts to 35 parts of polyisocyanate; 45 parts to 75 parts of flexible polyol; 10 parts to 15 parts of acrylate with active hydrogen; 2 parts to 5 parts of compound with interface anchoring group; and 0.1 part to 0.8 part of polymerization inhibitor.
4. The reactive toughening oligomer containing interface anchoring groups according to claim 3, characterized in that, The polyisocyanate is selected from at least one of hexamethylene diisocyanate, isophorone diisocyanate and 4,4'-dicyclohexylmethane diisocyanate; The flexible polyol is selected from at least one of polypropylene glycol, polytetrahydrofuran ether glycol, polyadipate diol, dimer acid polyester diol, polycarbonate diol and hydroxyl-terminated liquid polybutadiene; The acrylate with active hydrogen is selected from at least one of hydroxyethyl (meth)acrylate and hydroxypropyl (meth)acrylate; The compound with interface anchoring group is selected from at least one of hydroxyl-containing phosphoric acid compound, amino-containing phosphoric acid compound and hydroxyl-containing catechol compound; The polymerization inhibitor is selected from at least one of hydroquinone and p-tert-butylcatechol.
5. A method for preparing a reactive toughening oligomer containing interfacial anchoring groups as described in any one of claims 1 to 4, characterized in that, comprises the following steps: subjecting a flexible polyol to vacuum dehydration, then fully reacting polyisocyanate with the dehydrated flexible polyol at 75°C to 80°C under a protective atmosphere to obtain an isocyanate-terminated prepolymer; cooling to 45°C to 65°C, adding a polymerization inhibitor and mixing uniformly; then adding dropwise acrylate with active hydrogen at 45°C to 65°C, completing the dropwise addition within 1h to 2h, and then fully reacting at 55°C to 70°C; cooling to 45°C to 55°C, adding dropwise the compound with interface anchoring group, completing the dropwise addition within 1h to 2h, then fully reacting at 45°C to 55°C until the NCO content is ≤0.5%, which is regarded as qualified; and after qualification, cooling to 25°C to 30°C, filtering and discharging to obtain the reactive toughening oligomer containing interface anchoring group.
6. The reactive toughening oligomer containing interface anchoring groups according to claim 5, characterized in that, the time for full reaction of polyisocyanate and dehydrated flexible polyol at 75°C to 80°C is 3h to 4h; after adding dropwise the acrylate with active hydrogen, the time for full reaction at 55°C to 70°C is 1h to 2h; after adding dropwise the compound with interface anchoring group, the time for full reaction at 45°C to 55°C is 3h to 4h.
7. A two-component acrylic structural adhesive, characterized in that, comprises component A and component B: Component A comprises the following raw materials in parts by weight: 50-75 parts per unit; 5 to 15 parts of the oligomer as described in any one of claims 1 to 4; 0.1 to 1 part reducing agent; Toughening agent 10 to 30 parts; Polymerization inhibitor 0.1 to 1 part; 0.1 to 2 parts of filler; Component B comprises the following raw materials in parts by weight: Plasticizer 30-45 parts; 40 to 50 parts of oxidizing agent; Toughening agent 10 to 20 parts; Pigment 0.5 to 2 parts; 1 to 5 parts of filler.
8. The two-component acrylic structural adhesive according to claim 6, characterized in that, The monomer in component A is selected from at least one of methyl methacrylate, ethyl methacrylate, butyl methacrylate, methacrylic acid, and hydroxyethyl methacrylate. The reducing agent is selected from at least one of triethylamine and N,N-dimethyl-p-toluidine; The toughening agent is selected from at least one of nitrile rubber, chloroprene rubber, MBS resin, ABS resin, and SBS; The polymerization inhibitor is selected from at least one of hydroquinone, benzoquinone, naphthoquinone, and di-tert-butylmethylphenol; The filler is selected from fumed silica.
9. The two-component acrylic structural adhesive according to claim 6, characterized in that, The plasticizer in component B is selected from at least one of dioctyl dicarboxylate and dioctyl sebacate. The oxidant is benzoyl peroxide; The toughening agent is selected from at least one of nitrile rubber, chloroprene rubber, MBS resin, ABS resin and SBS; The filler is fumed silica; The pigment is phthalocyanine blue.
10. A method for preparing a two-component acrylic structural adhesive as described in any one of claims 5 to 9, characterized in that, Includes the following steps: Preparation of component A: Under a protective atmosphere, the reactive toughening oligomer containing interfacial anchoring groups, monomers and polymerization inhibitors are mixed evenly at 20℃~25℃. Then, toughening agent, reducing agent and filler are added and mixed evenly. Vacuum degassing is performed and the mixture is filtered out. Preparation of Component B: Under a protective atmosphere, plasticizer, oxidant, toughening agent, filler and pigment are mixed evenly at 20℃~25℃, vacuum degassing is performed, and the mixture is filtered out.